2019
DOI: 10.3390/catal9030265
|View full text |Cite
|
Sign up to set email alerts
|

Byproduct Analysis of SO2 Poisoning on NH3-SCR over MnFe/TiO2 Catalysts at Medium to Low Temperatures

Abstract: The byproducts of ammonia-selective catalytic reduction (NH3-SCR) process over MnFe/TiO2 catalysts under the conditions of both with and without SO2 poisoning were analyzed. In addition to the NH3-SCR reaction, the NH3 oxidation and the NO oxidation reactions were also evaluated at temperatures of 100–300 °C to clarify the reactions occurred during the SCR process. The results indicated that major byproducts for the NH3 oxidation and NO oxidation tests were N2O and NO2, respectively, and their concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…That is, catalyst poisoning only occurs at an ultra-low temperature. [29] For other SACs systems, the adsorption strength of C 6 H 10 would not cause this problem. As a result, it can be concluded that the PTA-supported Mn, Co, Ru, Rh and Pd SACs have a higher DÀ A reaction activity potential than Fe, Os, Ir and Pt systems, which may occur at ultra-low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…That is, catalyst poisoning only occurs at an ultra-low temperature. [29] For other SACs systems, the adsorption strength of C 6 H 10 would not cause this problem. As a result, it can be concluded that the PTA-supported Mn, Co, Ru, Rh and Pd SACs have a higher DÀ A reaction activity potential than Fe, Os, Ir and Pt systems, which may occur at ultra-low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 In addition, it has been found that SO 2 can also react with the metal oxides in the catalyst to form metal sulfates, which denature the active component and interrupt the SCR process by blocking the electron transfer path. 18 Fortunately, some effective strategies to alleviate the toxic effect of ABS have been investigated. Guo et al 19 found a significant accelerating effect on the decomposition of ABS by increasing the pore size of the material, which can greatly alleviate ABS deposition without chemical modifications.…”
Section: Introductionmentioning
confidence: 99%
“…So far, numerous low-temperature catalysts have been developed, including zeolites, transitional metal oxides, and rare-earth metal oxides. Among of them, MnO x catalysts have attracted increasing attention due to their low-temperature catalytic activities and low cost (Yang et al 2020;Lee et al 2019;Zhang et al 2019;). Nevertheless, MnO x catalysts still suffer from some challenging problems, such as narrow operation window, low N 2 selectivity, and poor resistance to H 2 O and SO 2 , which restricts their commercial application.…”
Section: Introductionmentioning
confidence: 99%